Pengaruh Metode Pembelajaran Crossword Puzzle terhadap Hasil Belajar Siswa pada Pembelajaran IPS di SMP Negeri 11 Semarang - Ayu Istiqomah; Siti Ekowati Rusdini (EduInovasi: Journal of Basic Educational Studies, 2025)
Low students' learning outcomes are still an issue in junior high school social studies instruction. This is due to teaching methods that do not involve student participation. Therefore, teachers need to select and apply innovative teaching methods to improve students' understanding of concepts. This study intends to explore the influence of crossword puzzles as a learning method on the learning results of seventh graders in IPS subjects at SMP N 11 Semarang. This study uses quantitative techniques and a nonequivalent control group design, which is a variation of a quasi-experimental design. The study’s sample comprised two classes, each with thirty-two students, Class VII B was the experimental group, and class VII D was the control group. The methods used to collect data included pre-test and post-test with essays and multiple-choice questions. The research instruments had undergone validity and reliability tests. Normality tests were used to analyze the data, homogeneity tests, and hypothesis tests with independent sample t-tests using SPSS version 25. The results showed that the average post-test score of the experimental class was 77.59, which was higher than that of the control class, which was 69.78. The hypothesis test showed a significance value of 0.010 (< 0.05), so H0 was rejected and Ha was accepted. Therefore, it can be said that the crossword puzzle learning approach significantly and favorably improves the social studies learning result of students at SMP N 11 Semarang.